PERLINDUNGAN KONSUMEN: KAJIAN HUKUM TERHADAP HP KW BERMEREK YANG TERDAFTAR DI PLATFORM E-COMMERCE SHOPEE. - Muchammad Galih Yuliansyah; Dwi Rangga Prasetyo; Erlin Septiyani; Ahmad Khayatudin (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Consumer protection is all efforts that ensure legal certainty to provide protection to consumers. The purposes of this study: 1) To find out and understand the legal protection for consumers against the purchase of counterfeit fake phone products obtained through the shopee marketplace. 2) To find out and develop an understanding of the responsibility carried out by Shopee for the losses experienced by consumers related to counterfeit fake phone products obtained through the Shopee marketplace. This study uses a library research method. While the data collection method uses the Normative method, The results of the study show that consumer protection against purchasing fake phone products through the Shopee marketplace: First, legal protection provided by Shopee to consumers in the form of obtaining comfort, security, goods safety, compensation if the goods do not match, and settlement of consumer protection disputes. Second, the compensation experienced by consumers is entirely the responsibility of the seller who opens a shop on the Shopee website, Shopee as a website provider only provides refund, return, and reshipment features as an intermediary for buyers and sellers.